Time-Awareness System for Managing Activities - Opoku, Samuel King; Otoo, Samuel (IJRDO -Journal of Computer Science Engineering, 2017)
Humans require reminder systems to prompt them into performing certain tasks. There are manyreminder systems designed to help humans. These applications fail to recognize users’ preference and interest.They, therefore, hardly handle multiple tasks at the same time. This study implements a time-awareness system thattakes into account prioritization of multiple tasks. The application accepts the various activities of the user includingtheir priority levels. When two or more applications crush, users’ preference and interest are used to select anddisplay the desired task. The application is implemented using Java Platform, Micro Edition